Managing software for growth : without fear, control, and the manufacturing mindset - Miller, Roy (Roy W.) (Addison-Wesley, 2003)
The IT professional's guide to delivering exceptional software development projects. One of the biggest problems facing businesses today is the effective delivery of software development projects. Recent surveys show that almost 75% of software development projects are either over budget, late, undeliverable, or cancelled outright. After more than 30 years of making software in an increasingly global economy dominated by technology, why is creating software still so hard? Software development expert Roy Miller answers this and other questions in Managing Software for Growth , the first truly insightful guide for industry observers and IT leaders who struggle to make great software despite the challenges. Contents include: The nature of the beast-why software projects fail, and what to do about it How rigor, formalism, and "science" have created barriers to software development Chaos, complexity, and emergence in complex adaptive systems Moving beyond the "manufacturing mindset," which makes no sense for software Practical advice on how to start growing software From philosophical evaluations of software engineering to nuts-and-bolts realism, Miller reveals the inner workings of the software development process in a way that will change the way people think about IT. Software development needs radical change to meet the challenges of the new century. For anyone involved in the process of software creation, Managing Software for Growth can help begin that process.